2015
DOI: 10.1186/s13063-015-0687-0
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine/propofol admixture (ketofol) at induction in the critically ill against etomidate (KEEP PACE trial): study protocol for a randomized controlled trial

Abstract: BackgroundEndotracheal intubation (ETI) is commonly performed as a life-saving procedure in the intensive care unit (ICU). It is often associated with significant hemodynamic perturbations and can severely impact the outcome of ICU patients. Etomidate is often chosen by many critical care providers for the patients who are hypotensive because of its superior hemodynamic profile compared to other induction medications. However, recent evidence has raised concerns about the increased incidence of adrenal insuffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 38 publications
0
15
0
1
Order By: Relevance
“…9 A recent example compared two induction agents for emergent bronchial intubation. 16 Cluster randomized studies are the other common case of RWOC. Sim and Dawson offer a detailed discussion, in which they further divide the category into cluster-cluster and individual-cluster research.…”
Section: Designs Based On Infeasibility Of Informed Consentmentioning
confidence: 99%
“…9 A recent example compared two induction agents for emergent bronchial intubation. 16 Cluster randomized studies are the other common case of RWOC. Sim and Dawson offer a detailed discussion, in which they further divide the category into cluster-cluster and individual-cluster research.…”
Section: Designs Based On Infeasibility Of Informed Consentmentioning
confidence: 99%
“…[42][43][44][45][46] Etomidate (0.3 mg/kg dose) has similar neutral hemodynamic effects but is associated with an increased incidence of adrenal insufficiency and mortality. 47 Ketofol and etomidate are being compared in an on-going clinical trial among critically ill patients. 47 Regardless of the choice of anesthesia, blood pressure should be monitored continuously and augmented as required until vessel recanalization is achieved.…”
Section: Review Volume Resuscitation Strict Blood Pressure Managemenmentioning
confidence: 99%
“…47 Ketofol and etomidate are being compared in an on-going clinical trial among critically ill patients. 47 Regardless of the choice of anesthesia, blood pressure should be monitored continuously and augmented as required until vessel recanalization is achieved. Arterial line placement should be considered for the duration of the procedure including induction for intubation, provided this does not result in a significant delay to endovascular stroke treatment.…”
Section: Reviewmentioning
confidence: 99%
“…A small retrospective cohort study assessed 240 intubated patients in the ED to quantify the relationship between SI with PIH and mortality [14]. The authors found that patients with a pre-intubation SI value of 0.8 or more were at higher risk of PIH (OR, 2.28; 95% CI, 1.18-4.43), but this value was not associated with a longer duration of intubation or higher in-hospital mortality.Kim et al conducted a retrospective study of 352 patients intubated in the ED to determine the risk factors for PIH [15]. The SI value was 0.68 for non-PIH patients and 0.79 for patients who developed PIH ( p <0.01).…”
Section: Introductionmentioning
confidence: 99%